Passive daylighting design strategies of colonial mosques in Malaysia - Sanusi, Aliyah Nur Zafirah; Abdullah, Fadzidah; Abdul Jamil, Ahmad Faisal; Othman, Rosniza (e-International Publishing House, Ltd., UK, 2021)
This study aims to investigate the daylight performance of Colonial Mosques in Malaysia. The first objective of this study is to identify passive daylighting strategies from colonial mosques. The second objective of this study is to evaluate the daylight performance of the colonial mosques. The research methodology consisted of table research, field observation, and daylight analysis simulation of the prayer hall in the Colonial Mosques, using Sefaira daylighting simulation software. The results have shown that the daylight in Colonial Mosques was affected by the building orientation, shading elements, window to wall ratio, and window type. In conclusion, the clerestory window type enhances indoor daylight performance.